Parametric Optimization of Microwave Reflux Extraction of Spice Oleoresin from White Pepper (Piper nigrum) - Olalere, Olusegun Abayomi; Nour, A. H.; Alara, Oluwaseun Ruth; Habeeb, Omar Abed (Springer Open, 2017)
Background: White Piper nigrum is an important commodity crop containing a number of essential bioactive components with nutritional and medicinal properties when sufficiently extracted. Microwave refluxation is therefore a novel technique employed in the extraction of bioactive components from natural products of plant origin. This method doubled as classical and traditional solvent extraction techniques with reduced extraction time, higher selectivity, low solvent consumption, and higher extraction rate.